The iR2 regimen (ibrutinib plus lenalidomide and rituximab) for relapsed/refractory DLBCL: a multicentre, non-randomised, open-label phase 2 study. (February 2023) - Ramchandren, Radhakrishnan; Johnson, Peter; Ghosh, Nilanjan; Ruan, Jia; Ardeshna, Kirit M.; Johnson, Roderick; Verhoef, Gregor; Cunningham, David; de Vos, Sven; Kassam, Shireen; Fayad, Luis; Radford, John; et al.
Summary: Background: This phase 1b/2 PCYC-1123-CA study evaluated efficacy and safety of the combination of ibrutinib, lenalidomide, and rituximab (iR 2 regimen) in patients with relapsed/refractory diffuse large B-cell lymphoma (DLBCL) ineligible for stem cell transplantation. Methods: In phase 2, patients with relapsed/refractory non-germinal centre B-cell–like DLBCL received oral ibrutinib 560 mg once daily and oral lenalidomide 20 mg or 25 mg once daily on Days 1–21 of each 28-day cycle until disease progression or unacceptable toxicity and intravenous rituximab 375 mg/m 2 on Day 1 of Cycles 1–6. The primary endpoint was overall response rate (ORR) in the response-evaluable population (received any study treatment and had ≥1 post-baseline disease assessment). The study was done at 24 academic and community hospitals in Belgium, Germany, United Kingdom, and USA. This study was registered with ClinicalTrials.gov, NCT02077166. Findings: Between March 13, 2014 and October 2, 2018, 89 patients were enrolled with a median time on study of 35.0 months. Best ORR in the response-evaluable population (n = 85) was 49% (95% confidence interval [CI], 38–61) across dose cohorts and 53% (95% CI, 39–67) and 44% (95% CI, 26–62) in the 20 mg and 25 mg lenalidomide cohorts, respectively, with complete responses in 24/85 (28%), 17/53 (32%), and 7/32 (22%) patients, respectively. Grade 3/4 adverse events (AEs) occurred in 81/89 patients (91%), most frequently neutropenia (36/89; 40%), maculopapular rash (16/89; 18%), anaemia (12/89; 13%), and diarrhoea (9/89; 10%). Serious adverse events occurred in 57/89 patients (64%). Fatal AEs occurred in 12/89 patients (13%); causes of death were worsening of DLBCL (n = 7), pneumonia (n = 3), sepsis (n = 1), and cardiac arrest (n = 1). Interpretation: The most frequent AEs (diarrhoea, neutropenia, fatigue, cough, anaemia, peripheral oedema, and maculopapular rash) were consistent with known safety profiles of the individual drugs. The iR 2 regimen demonstrated antitumour activity with durable responses in patients with relapsed/refractory DLBCL. Funding: Pharmacyclics LLC, an AbbVie Company.